Characterization and FDTD simulation analysis on light trapping structures of amorphous silicon thin films by laser irradiation. (May 2016) - Huang, Lu; Jin, Jing; Yuan, Zhijun; Yang, Weiguang; Wang, Linjun; Shi, Weimin; Zhou, Jun; Lou, Qihong
Abstract: The effect of laser energy density on the light-trapping structures of amorphous silicon (α-Si) thin films is studied both theoretically and experimentally. The thin films are irradiated by a frequency-doubled (λ = 532 nm) Nd:YAG pulsed nanosecond laser. An effective finite difference time domain (FDTD) model is built to find the optimized laser energy density (EL ) for the light trapping structures of α-Si. Based on the simulation analysis, it shows the variation of reflection spectra with laser energy density. The optimized reflection spectra at EL  = 1000 mJ/cm 2 measured by UV–visible spectroscopy confirms to agree well with that corresponding to the depth to diameter ratio (h/D) in the FDTD simulation. The surface morphology characterization by optical microscope (OM) and scanning electron microscope (SEM) accords fairly well to of light-trapping modeling in the simulation. Graphical abstract: Highlights: The light trapping structures of α-Si thin film are formed by pulsed laser irradiation. Different reflection spectra corresponding to h/D are obtained by FDTD simulation. Reflection spectra with different structure are measured by UV–visible spectroscopy. The morphology characterization verifies light-trapping modeling in the simulation.